Exposure to Closed Loop Barriers Using Virtual Reality. (September 2020) - Lanning, Monica; Shen, Jessica; Wasser, Daniel; Riddle, Scott; Agustin, Bianca; Hood, Korey; Naranjo, Diana
Background: Closed loop (CL) automated insulin delivery systems are demonstrated to be safe and effective in regulating glucose levels and reducing cognitive burden in people with type 1 diabetes (T1D). However, given the limited market options and the do-it-yourself nature of most systems, it can be difficult for potential users to shape their expectations fitting them into daily lives and management routines. As such, we examined the potential feasibility of a virtual reality (VR) intervention. Methods: A four-part VR intervention was created to expose adults with T1D to expected CL system barriers: body image, perceived hassles of using CL, deskilling fears, and unwanted social attention. Goals of the pilot were to assess feasibility and expose patients to CL. Surveys were conducted pre- and postparticipating in the VR experience. Results: A total of 20 adults with T1D completed the pilot. Average time to complete the experience was 14.1 minutes (8.8-39.9). Reported VR sickness was low. Willingness to use VR was maintained in 90% ( n = 18) and did not change expectations of CL in 95% ( n = 19). Virtual reality changed perceived hassles of CL in 25% ( n = 5) with four concerned over alarms and one connectivity issues: positive diabetes technology attitudes, confidence in managing hypoglycemia, overall perceptions of appearance, and positive affect maintained after the VR intervention. Negative affect significantly decreased after exposure and perceptions of being overweight trended toward significance. Conclusion: This pilot VR intervention demonstrated high potential in addressing expected barriers to uptake and usage of CL systems without decreasing enthusiasm or changing expectations of CL.